Responsibility Parking Service Business to The Protection Of Consumer Of The Parking Services in Makassar - Andika Prawira Buana; Aan Aswari; Muh Fachri Said; Muhammad Ya'rif Arifin (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2018)
The development of dynamic human behavior will lead to more complex contractual relationships. A contractual relationship that occurs must necessarily be accompanied by certainty and legal protection for each party. Existing regulations should serve as guidelines for contractual relationships. Parking business practitioners and parking service users must understand and know the rights and obligations of each. The form of liability which must be fulfilled by each party shall be adhered to in order to create a good contractual relationship and the fulfillment of rights and obligations based on the prevailing laws and regulations. This research is research with qualitative type with the socio-juridical approach. This study responded the ineffectiveness of the accountability of parking service business actors (PD Parkir Makassar Raya) to the consumer protection of parking service users because there is still a standard clause on the parking ticket. Makassar City Local Government needs to provide direct supervision on policies issued by PD Parkir Makassar Raya and revise the Local Regulation on Parking Management in order to be relevant to the provisions of the higher Legislation (UUPK). Parking service users are also required to increase legal awareness to know what rights and obligations of service users and parking service business actors.